Pengaruh PAD, Jumlah Penduduk, Jumlah Investasi, dan Jumlah Pencari Kerja terhadap PDRB Kabupaten Kuningan - Happy Nurmayanti; Istiqomah Subechan; Lilis Siti Badriah (Universitas Batanghari Jambi, 2021)
This study is a study of the effect of PAD, population, investment, and number of job seekers on the GRDP of Kuningan Regency. The purpose of this study was to analyze the effect of PAD, population, total investment, and number of job seekers on the GRDP of Kuningan Regency. The data used is secondary data by taking time series data from 2010 to 2019. The variables used in this study are PAD, total population, total investment, and number of job seekers. Analysis of the data used in this study is OLS with = 0.05. The results of this study partially indicate that the number of job seekers has a significant effect on the GRDP of Kuningan Regency, while PAD, population, and the amount of investment have no significant effect on the GRDP of Kuningan Regency.